On the Need for a Tsunami Warning System in the North East Atlantic Area (Gulf of Cadiz) - A., Baptista M.; R., Omira; L., Matias; M., Miranda J.; A., Annunziato; F., Carrilho; F., Kaabouben (IntechOpen, 2011)
None